Gresham's Law and News in a Post-Truth World. (June 2019) - Kovacic, Branislav
Economists and finance experts have studied how 'bad money drives out good' and formulated Gresham's law (Mokyr, 2003). The law states that the more expensive money tends to disappear from circulation because it is counterfeited, hoarded, or exported. One can propose a similar principle in the news business – real, verified, and socially relevant news tends to be replaced by fake, unverified, and often socially irrelevant news. This tends to happen not only in the American version of news production models (purportedly neutral and objective) but also in other more ideologically and politically oriented news production models.